2013
DOI: 10.1111/j.1743-498x.2012.00607.x
|View full text |Cite
|
Sign up to set email alerts
|

A method for identifying extreme OSCE examiners

Abstract: Of 3000+ raters, fewer than 0.3% have been identified as being extreme using the proposed criteria. Rater performance is being monitored on a regular basis, and the impact of these raters on candidate results will be considered before results are finalised. Extreme raters are contacted by the organisation to review their rating style. If this intervention fails to modify the rater's scoring pattern, the rater is no longer invited back. As more data are collected the organisation will assess them to inform the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 11 publications
0
34
0
Order By: Relevance
“…These include work-based assessments, oral examinations and OSCEs [58]. Although extreme differences in examiner severity are probably relatively uncommon [9] modest differences in examiner severity may make important differences to student grades and pass-fail decisions.…”
Section: Introductionmentioning
confidence: 99%
“…These include work-based assessments, oral examinations and OSCEs [58]. Although extreme differences in examiner severity are probably relatively uncommon [9] modest differences in examiner severity may make important differences to student grades and pass-fail decisions.…”
Section: Introductionmentioning
confidence: 99%
“…The nature of these case studies (revealed through post hoc analysis) meant we were unable to perform direct observation of the assessor-candidate encounters to better understand the challenges of a complex performance assessment, nor undertake detailed O"CE Whilst the number of cases we are able to present in this work is small, the impact of these particularly for pass/fail decisions in the critical region, reflecting the findings of others (Bartman et al 2013). It is also tempting to postulate that such problems would not arise through the use of global grades only (as employed by many institutions), but we would argue that the use of key feature scoring/checklist formats and global grades allowed the generation of sophisticated station level metrics which consequently aided in detection and categorisation of assessor judgements judged to be at the extreme .…”
Section: Discussionmentioning
confidence: 75%
“…Small bodies of work have started to concentrate on identifying examiners that are at the extremes of marking at station level, revealing in one study that <0.3% of examiners can be classed as extreme [ three standard deviations beyond the mean of all raters] (Bartman et al 2013). Whilst the overall proportion in these case studies, it are a reflection of a complex environment which exerts powerful effects on assessment through test constructs and scoring formats and judgements about safe clinical care (Kogan et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We only retrospectively collected a limited amount of candidates' self-reported Examinations Committees with the endorsement of the Executive Committee of the ESICM decided to perform a series of measures in order to further improve the quality and standardization of the EDIC exam. This includes: (1) unification of the electronic database system to allow prospective candidates' data collection and regular exam outcome evaluation; (2) introducing the individual examiner's performance monitoring 12 ; (3) introducing a scheme of regular examiners' rotations among centres; (4) gaining accreditation of The Council for European Specialists Medical Assessment (CESMA) for the EDIC exam.…”
Section: Discussionmentioning
confidence: 99%